Analysis of the Influence of Economic Growth, Education and Unemployment on Poverty - Mahaputra, M. Rizky; Mahaputra, M. Ridho; Maharani, Amalina (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The problem in this research is the effect of economic growth, education and unemployment on poverty levels. This type of research is descriptive and associative research through secondary data. The results showed that (1) economic growth had a negative and significant effect on poverty by -1.4409 percent with a probability value = 0.00 2 (2) education had a negative and significant effect on poverty by -0.4376 percent with a probability value = 0. 006 (3) Unemployment has a positive and insignificant effect on poverty by 0.502 percent with a probability value = 0.1771.